Dasatinib and Azacitidine Followed by Haploidentical Stem Cell Transplant for Chronic Myeloid Leukemia with Evolving Myelodysplasia: A Case Report and Review of Treatment Options - Lang, Fabian (Am J Case Rep, 2017)
Patient: Female, 41 Final Diagnosis: CML with myelodysplasia Symptoms: Fatigue Medication: Dasatinib • Azacitidine Clinical Procedure: Haploidentical stem cell transplantation Specialty: Hematology OBJECTIVE: Rare co-existance of disease or pathology BACKGROUND: CML presenting with a variant Philadelphia translocation, atypical BCR-ABL transcript, additional chromosomal aberrations, and evolving MDS is uncommon and therapeutically challenging. The prognostic significance of these genetic findings is uncertain, even as singular aberrations, with nearly no data on management and outcome when they coexist. MDS evolving during the course of CML may be either treatment-associated or an independently coexisting disease, and is generally considered to have an inferior prognosis. Tyrosine kinase inhibitors (TKI) directed against BCR-ABL are the mainstay of treatment for CML, whereas treatment modalities that may be utilized for MDS and CML include allogeneic stem cell transplant and – at least conceptually – hypomethylating agents. CASE REPORT: Here, we describe the clinical course of such a patient, demonstrating that long-term combined treatment with dasatinib and azacitidine for coexisting CML and MDS is feasible and well tolerated, and may be capable of slowing disease progression. This combination therapy had no deleterious effect on subsequent potentially curative haploidentical bone marrow transplantation. CONCLUSIONS: The different prognostic implications of this unusual case and new therapeutic options in CML are discussed, together with a review of the current literature on CML presenting with different types of genomic aberrations and the coincident development of MDS. Additionally, this case gives an example of long-term combined treatment of tyrosine kinase inhibitors and hypomethylating agents, which could be pioneering in CML treatment.